PERTUMBUHAN EKONOMI: ANALISIS INDUSTRI HALAL DAN ASET KEUANGAN SYARIAH DI NUSA TENGGARA BARAT (NTB) - Imsar, Imsar; Silalahi, Purnama Ramadani; Fattah, Abdul (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2024)
A halal lifestyle should not just be a trend in Indonesia. A halal lifestyle should be the most important and inseparable part of all aspects of our lives, be it food and drink, medicine, tourism, beauty, energy and so on. The aim of this research is to analyze the short-term and long-term influence of the halal industry and sharia financial assets on economic growth in NTB, the potential development of the halal industry and the challenges and obstacles in this regard. The method used in this research is a Mix Method research method, namely using a quantitative approach with the Vector Autoregressive (VAR) Model and a qualitative approach, namely in-depth interviews (in-depth interviews). From this research, the results obtained are that the halal industry has a positive and significant effect on the economic growth of West Nusa Tenggara Province. Assets of sharia financial institutions have no effect on the economic growth of West Nusa Tenggara Province.